Behandlingen av ord på -erska och -inna i SAOB - Mattisson, Ann-Christin (Nordiske Studier i Leksikografi, 2003)
This paper is dealing with the different treatment of feminine words or derivatives in -(er)ska and -inna in the Dictionary of the Swedish Academy (SAOB). The material comprises around 300 examples where the derivatives in -(er)ska and -inna have the same base (målerska, målarinna to the verb måla or the masculine designation målare).